Bisexual Latino Men's Motivations for Sex. Issue 4 (2nd October 2019) - Muñoz-Laboy, Miguel; Garcia, Jonathan
Abstract: Motivations for bisexual Latino men to have sex have been often overlooked in sexuality education research. This analysis examined the associations between motivations for sex (using the AMORE questionnaire) with a sample of 148 bisexual Latino men. We found that (1) depression was positively associated with sex to relieve stress; (2) machismo was positively associated with power-related sex for stress relief, pleasure, and, nurturance motives for sex; (3) procreative motives for sex were associated with perceived stress and not associated with familismo or religiosity. We conclude by presenting implications for sexuality education and therapeutic services for bisexual Latino men.